2020
DOI: 10.20944/preprints202011.0524.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Zinc Finger Linkers in Zinc Finger Protein Binding to DNA

Abstract: Zinc finger proteins (ZFP) play important roles in cellular processes. The DNA binding region of ZFP consists of 3 zinc finger DNA binding domains connected by amino acid linkers, the sequence TGQKP connects ZF1 and ZF2, and TGEKP connects ZF2 with ZF3. Linkers act to tune the zinc finger protein in the right position to bind its DNA target, the type of amino acid residues and length of linkers reflect on ZF1-ZF2-ZF3 interactions and contribute to the search and recognition process of ZF protein to its DNA tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…1) For a certain ZnF, its preferably bound DNA triplets in live cells cannot be predicted accurately [24]. It has been found that besides those "fingerprint" amino acids, other nearby amino acids including the linker sequences also contribute to the DNA binding activity [17,18,25]. 2) It is commonly observed that not all the ZnF individuals within a tandem array are actually involved in the target recognition while the intrinsic rule of this selective usage is largely unknown [26].…”
Section: Introductionmentioning
confidence: 99%
“…1) For a certain ZnF, its preferably bound DNA triplets in live cells cannot be predicted accurately [24]. It has been found that besides those "fingerprint" amino acids, other nearby amino acids including the linker sequences also contribute to the DNA binding activity [17,18,25]. 2) It is commonly observed that not all the ZnF individuals within a tandem array are actually involved in the target recognition while the intrinsic rule of this selective usage is largely unknown [26].…”
Section: Introductionmentioning
confidence: 99%